High-entropy spinel-structure oxides as oxygen evolution reaction electrocatalyst - Stenzel, David; Zhou, Bei; Okafor, Chukwudalu; Kante, Mohana Veeraju; Lin, Ling; Melinte, Georgian; Bergfeldt, Thomas; Botros, Miriam; Hahn, Horst; Breitung, Ben; Schweidler, Simon (Frontiers in Energy Research, 2022)
High-entropy oxides are an upcoming research topic due to their broad range of possible crystal structures and applications. In this work, we want to present the change in the catalytic properties when using different elements to create a high-entropy spinel. Therefore, we used the nebulized-spray pyrolysis to synthesize the high-entropy spinel (Mn0.2Fe0.2Ni0.2Mg0.2Zn0.2)3O4 and later on exchanged the Mg or the Zn with elements with multiple possible oxidation states, in our example each with Cr or Co. The phase purity, morphology, microstructure and homogeneity were investigated by XRD, SEM and STEM-EDX. Their electrocatalytic performance and stability was measured via oxygen evolution reaction and cyclic voltammetry and compared to IrO2, used as reference. The best performance of the synthesized materials was achieved by (Mn0.2Fe0.2Ni0.2Mg0.2Cr0.2)3O4.